PASTURE RENEWAL BY DIFFERENT MECHANIZED ASSEMBLIES - Magalhães, A. C.; Moreira, B. R. A.; de Figueiredo, P. A. M.; da Fonseca, R.; Parra, F. S.; Yamamoto, W. K. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The aim of this study is to assess the renewal of Urochloa decumbens pasture for the cultivar Urochloa brizantha (Syn. Brachiaria brizantha) cv. Marandu by means of different sowing processes. Three different treatments were herein assed as follow: conventional sowing with a plowing and two harrowing; direct sowing in line under straw; and minimum sowing with two harrowing, in two productive cycles and five consecutive cuts. The number of tillers per plants after pasture emergence, the soil cover rate and the plant height were determined. The total dry matter yield was obtained by the sum of the productions of the cuts during the productive cycle of the pasture. The experimental design was completely randomized blocks with three replicates. The results were submitted to analysis of the variance and the means of the treatments were compared by the Tukey test at 5 % of significance. The best performance of the establishment and the highest values of dry matter yield of Urochloa brizantha cv. Marandu pasture were obtained in the systems of conventional and minimum sowing, when compared with the direct sowing.